The Short-Term Distributional Effects of the German Minimum Wage Reform - Marco Caliendo; Alexandra Fedorets; Malte Preuß; Carsten Schröder; Linda Wittbrodt (Institute of Labor Economics (IZA), 2017)
This study quantifies the short-term distributional effects of the new statutory minimum wage in Germany. Using detailed survey data (German Socio-Economic Panel), we assess changes in the distributions of hourly wages, contractual and actual working hours, and monthly earnings. Our descriptive results indicate growth at the bottom of the hourly wage distribution in the post-reform year, but also considerable noncompliance among eligible employees. In a second step, we employ a difference-in-differences analysis and exploit regional variation in the "bite" of the intervention, measured by the share of employees in a geographical region with wages below the minimum wage prior to the reform. We document the reform's positive effect at the bottom of the wage distribution. However, we find a negative effect of the reform on contractual hours worked, which explains why there is no effect on monthly earnings. Given that actual hours worked decrease less than contractual hours, our evidence suggests an increase in unpaid overtime.
Keywords: J31; J38; J22; 330; minimum wage; wage distribution; hourly wages; inequality